ANALISIS POWER YANG DIPERLUKAN PADA RANCANG BANGUN ALAT BANTU SENAI PORTABEL - Eko Arif Syaefudin; Aam Amaningsih Jumhur; Dyah Arum Wulandari; Muhammad Alfian Dwi Putra Putra; Wardoyo (Jurnal Konversi Energi dan Manufaktur, 2022)
Machines as tools in human work are currently the main needs that need to be in the goods and service industry. The machine as a tool based on its use is divided into 2 types, namely permanent/static and mobility/portable. Permanent machines are more widely used in the industrial world, while portable machines are more for repair services, which require various locations that are sometimes difficult to reach, and the application position can operate properly, and save time, energy, operational costs, and can be used anywhere. The weakness of portable machines lies in the power used because the power source uses mostly batteries. For this reason, further research is needed to obtain an analysis of the appropriate power requirements in the field. The steps taken in this study used experimental research methods to obtain results relevant to the power used according to the design needs of the tool. Control and power design analysis uses components such as DC electric motors, switches, adapters, and infrared sensors. From the results of the analysis of the control and power design calculations, the results obtained in the calculation of the electric motor power of 114 W (general power used in portable drilling machines) and the calculation of torque of 6.5 Nm the capacity in making external threads using this tool is capable of a maximum diameter of M6 with ST41 material.